Residential field site training project abstracts - 45th Batch Session: 2002-2003 4th year MBBS Students, CMC (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v18i2.3840Journal of Chittagong Medical College Teachers' Association 2007: 18(2):58-62